Question
\begin{tabular}{l} Solve for \( y \). \\ \( \qquad(3+y) h=C \) \\ \( y=\square \) \\ \hline\end{tabular}
Ask by Elliott Burton. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( y = \dfrac{C}{h} - 3 \)
Solution
Sure, let's solve for \( y \) step by step and complete the provided table.
\[
\begin{tabular}{l}
\textbf{Solve for } \( y \). \\
\( \qquad(3 + y) h = C \) \\
\( y = \dfrac{C}{h} - 3 \) \\
\hline
\end{tabular}
\]
**Steps to Solve for \( y \):**
1. Start with the equation:
\[
(3 + y) h = C
\]
2. Divide both sides by \( h \) to isolate \( 3 + y \):
\[
3 + y = \dfrac{C}{h}
\]
3. Subtract 3 from both sides to solve for \( y \):
\[
y = \dfrac{C}{h} - 3
\]
So, the solution for \( y \) is:
\[
y = \dfrac{C}{h} - 3
\]
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Mind Expander
First, let’s isolate \( y \) in the equation \( (3 + y)h = C \). To do this, divide both sides by \( h \) (assuming \( h \neq 0 \)), giving us \( 3 + y = \frac{C}{h} \). Now, subtract 3 from both sides to find that \( y = \frac{C}{h} - 3 \). So, the solution is: \[ y = \frac{C}{h} - 3 \]